Early New Testament apocrypha - Edwards, J. Christopher., 1982- (Zondervan Academic, Grand Rapids, Michigan, 2022)
"Early New Testament Apocrypha, in the Ancient Literature for New Testament Studies series, seeks to introduce key ancient texts that form the cultural, historical, and literary context for the study of the New Testament"--
"Broaden the scope of your New Testament studies with this introduction to early Christian apocryphal literature.To understand the New Testament well, it is important to study the larger world surrounding it, and one of the primary avenues for this exploration is through reading related ancient texts. But this task is daunting for scholars and novices alike given the sheer size of the ancient literary corpora. The Ancient Literature for New Testament Studies series aims to bridge this gap by introducing the key ancient texts that form the cultural, historical, and literary context for the study of the New Testament.Early New Testament Apocrypha offers an entry point into the corpus of early Christian apocryphal literature through twenty-eight texts or groups of texts. While the majority of the texts fall within the first four centuries CE, and therefore are useful for uncovering the earliest interpretations assigned to the New Testament, select later texts serve as reminders of how the meanings of New Testament texts continued to develop in subsequent centuries. Each essay covers introductory matters, a summary of content, interpretive issues, key passages for New Testament studies and their significance, and a select bibliography.Whether you are a scholar looking to familiarize yourself with a new corpus of texts or a novice seeking to undertake a serious contextualized study of the New Testament, this is an ideal reference work for you. --
Part 1: Apocryphal Gospels. Agrapha / Andrew Gregory -- Gospel Fragments on Papyrus / Tobias Nicklas -- Gospel of Barnabas / Philip Jenkins -- Gospel of Peter / Paul Foster -- Infancy Gospel of Thomas / Reidar Aasgaard -- Jewish-Christian Gospels / Petri Luomanen -- Legend of Aphroditian / Katharina Heyden -- Pilate Cycle / J. K. Elliott -- Protevangelium of James / Eric M. Vanden Eykel -- Toledot Yeshu / Sarit Kattan Gribetz -- Revelation of the Magi -- Catherine Playoust. Part 2: Apocryphal Acts. Acts of Andrew / Nathan C. Johnson -- Acts of John / Harold W. Attridge -- Acts of Paul / Harold W. Attridge -- Acts of Peter / Robert F. Stoops, Jr. -- Acts of Philip / Christopher R. Matthews -- Acts of Thomas / Harold W. Attridge -- Departure of My Lady Mary from This World (Six Books Dormition Apocryphon) / J. Christopher Edwards -- Pseudo-Clementines / F. Stanley Jones. Part 3: Apocryphal Epistles. Jesus's Letter to Abgar / William Adler -- Correspondence of Paul and Seneca / Andrew Gregory -- Epistle to the Laodiceans / Philip L. Tite -- Epistula Apostolorum / Florence Gantenbein -- The Sunday Letter / Jon C. Laansma. Part 4: Apocryphal Apocalypses. Apocalypse of Paul / Jan N. Bremmer -- Apocalypse of Peter (Greek) / Dan Batovici -- Apocalypse of Thomas / Mary Julia Jett -- First Apocryphal Apocalypse of John / Robyn J. Whitaker -- Conclusion. New Testament Apocrypha: Introduction and Critique of a Modern Category / Dale B. Martin.
Includes bibliographical references and index.
Keywords: Apocryphal books (New Testament) -- Criticism, interpretation, etc; RELIGION / Biblical Reference / Handbooks; RELIGION / Biblical Studies / New Testament / General